2016
DOI: 10.4048/jbc.2016.19.4.394
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Inner Quadrant Involvement in Breast Cancer Treated with Neoadjuvant Chemotherapy

Abstract: PurposeIn the present study, we aimed to evaluate the initial tumor location as a prognostic factor in breast cancer patients treated with neoadjuvant chemotherapy (NAC).MethodsBetween March 2002 and January 2007, a total of 179 patients with stage II/III breast cancer underwent NAC followed by breast surgery. Using physical and radiologic findings, patients were grouped by their initial tumor location into inner/both quadrant (upper/lower inner quadrant involvement +/− multicentric tumor involving outer quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As a result, the five-year survival rate of IDC patients will be reduced, and the five-year survival rate of patients with primary tumors located in the central area, the inner upper quadrant, and inner lower quadrant will be lower than that of patients located in the outer upper quadrant and outer lower quadrant. In addition, due to the excessive penetration of mammography to the nipple-areolar complex, tumors in the central region are often overlooked, requiring the combination of multiple imaging techniques [ 28 ]. The molybdenum target detection rate of breast cancer in the central region is low, and the tumor is detected in a late stage, which delays the treatment time and reduces the five-year survival rate of patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the five-year survival rate of IDC patients will be reduced, and the five-year survival rate of patients with primary tumors located in the central area, the inner upper quadrant, and inner lower quadrant will be lower than that of patients located in the outer upper quadrant and outer lower quadrant. In addition, due to the excessive penetration of mammography to the nipple-areolar complex, tumors in the central region are often overlooked, requiring the combination of multiple imaging techniques [ 28 ]. The molybdenum target detection rate of breast cancer in the central region is low, and the tumor is detected in a late stage, which delays the treatment time and reduces the five-year survival rate of patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with lower quadrants, we elucidated the favorable prognostic value of upper quadrants in various subgroups of breast cancer patients. Accordingly, pertinent studies have reported better prognosis of patients with tumors in UOQ [23,8], and tumors in LIQ have been veri ed as worse prognostic factor in breast cancer [24,12]. Anatomically, the lymphatics from the lower portion of the breast appear to occasionally communicate with those under the diaphragmatic region or peritoneal plexus by passing through the sheath of rectus abdominis, and Kamakura and colleagues [21] revealed that a lower quadrants tumor location was a signi cant prognostic factor for recurrence, especially soft tissue and visceral recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the retrospective study by Chang et al (1), tumor site affects the survival of breast carcinoma patients who received NAC for the first time. Unlike the earlier clinical trials, our study primarily focused on three significant quadrants in our NAC setting.…”
Section: Discussionmentioning
confidence: 99%
“…The poor prognosis of lower-inner quadrant breast cancer in patients who received neoadjuvant chemotherapy occurrence, inner-quadrant cancer is often characterized by poor prognosis and shorter breast cancer-specific survival (BCSS) and overall survival (OS). Nevertheless, the study conducted by Chang et al (1) was the only clinical study to explore the prognostic value of tumor size on the survival of breast cancer patients who received NAC treatment. Moreover, the clinical trial conducted by Jiqiao Yang revealed that tumors in the lower-inner zone (LIZ) had a markedly poor prognosis in terms of disease-free survival (DFS) in patients in the NAC subgroup.…”
Section: Original Articlementioning
confidence: 99%